1979
DOI: 10.1210/endo-104-4-908
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lithium on Bone Metabolism in Organ Culture*

Abstract: The effects of lithium on bone metabolism were determined using different organ culture models for the study of resorption and collagen synthesis. At concentrations of 3 X 10(-3)--10(-2) M, lithium blocked the stimulation of 45Ca and lysosomal enzyme release by parathyroid hormone (PTH) but did not affect bone resorption in control cultures in the absence of PTH. Lithium inhibition was observed in continuous culture with PTH or when bones were exposed to both agents for only 8 h. Lithium was less effective in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Lithium can affect CAMP-dependent events in various cell types (Dousa and Hechter, 1970;Anderson and Blackard, 1978;Gibson et al, 1979;Holak and Raisz, 1979). Recently lithium was also reported to abrogate CAMP-dependent events in human lymphocytes induced by cAMP activators but not by dibutyryl cAMP (Gelfand et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Lithium can affect CAMP-dependent events in various cell types (Dousa and Hechter, 1970;Anderson and Blackard, 1978;Gibson et al, 1979;Holak and Raisz, 1979). Recently lithium was also reported to abrogate CAMP-dependent events in human lymphocytes induced by cAMP activators but not by dibutyryl cAMP (Gelfand et al, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Holak and Raisz [40], studying the effects of lithium on bone metabolism, demonstrated that lithium does not inhibit the incorporation of labeled proline in collagen and noncollagen protein. Collagen types synthesized by murine bone marrow cells and the effect of lithium chloride on collagen biosynthesis have been studied in vitro experiments [41].…”
Section: Bonementioning
confidence: 99%
“…The effects of lithium on the cellular level have only begun to be extensively investigated within the last decade [17À19]. Studies on side effects concern the haemopietic tissues [20], kidneys [21À23], bone metabolism [24], and skin [25À30].…”
Section: Introductionmentioning
confidence: 99%